Tokens for the foundlings - Curtis, Tony 1955- (Seren, 2012)
This collection of poetry is divided into three sections: orphans and foundlings, infancy, and early childhood, and includes poems contributed by Carol Ann Duffy, Seamus Heaney, Gillian Clarke, and Stephen Knight
Anthology of poems about orphans, childhood and family published in support of the Foundling Museum in Bloomsbury
Keywords: Foundling Museum; Children / Poetry; Foundlings / Poetry; Families / Poetry; Orphans / Poetry; Kind